A QUALITATIVE STUDY EXPLORING MEANINGFUL IMPROVEMENT IN BOWEL URGENCY AMONG ADULTS WITH MODERATE TO SEVERE ULCERATIVE COLITIS. (22nd January 2022) - Newton, Louise; Guobyte, Aiste; McFadden, Shehan; Symonds, Tara; Delbecque, Laure; Donaldson, Jill; Naegeli, April
Abstract: BACKGROUND: Ulcerative Colitis (UC) is a chronic disease with periods of relapse and remission. Bowel urgency, the sudden or immediate need for a bowel movement, is one of the most bothersome symptoms experienced by patients with UC. This study explored how patients define urgency severity and what would be a meaningful improvement based on a numeric rating scale (NRS). METHODS: In-depth interviews were conducted in the United States with 19 adults with clinician-confirmed moderate to severe UC. Participants were asked to define levels of bowel urgency severity using an 11-point NRS (where 0 = no urgency and 10 = worst possible urgency) and to describe what would be a meaningful improvement based on how this change would impact their daily life. Interviews were audio-recorded, transcribed, and coded using thematic coding in NVivo. RESULTS: Mild bowel urgency was described as ranging between 0 to 3 on the 11-point scale by most UC patients (n=16, 84%). Mild was described as "almost normal" or "normal urgency" (n=6, 32%) and being able to make it to the bathroom with ease (n=5, 25%). Most participants (n=15, 79%) rated moderate urgency between 4 to 6 on the 11-point scale. At this level, participants commented that they would need to ensure they are close to a bathroom (n=7, 37%). Finally, ratings for severe urgency clustered between 6 to 8 (n=7, 37%) and 8 to 10 (n=12, 63%). Severe bowel urgency was described as an immediate or uncontrollable need (n=8, 42%) which impacts their ability to leave the home (n=7, 37%). When asked about what change on the urgency NRS would be meaningful, n=10 (53%) participants reported that a 1-point change would be meaningful, with most stating that any change was an improvement. Participants commented that a 1-point change would reflect improved emotional well-being and greater confidence to leave the home. In contrast, 9 (47%) participants wanted improvements of more than 1-point change; 5 (26%) indicated that a 2-point improvement was required to consider the change meaningful and 4 (21%) felt a 3-point change or more was needed. With this greater level of change, participants described having a significant improvement in urgency, with less frequent urges and improved emotional well-being. CONCLUSION: This qualitative study revealed that UC patients largely agreed regarding ratings of 'mild' and 'moderate' bowel urgency on an 11-point severity scale. 'Severe' bowel urgency was split between two ranges suggesting the existence of 'very severe' bowel urgency. In addition, the majority of UC patients perceived a 1 or 2-point reduction on the urgency NRS as a meaningful change in their lives.